i dont know
2007-01-17 23:21:21
·
answer #1
·
answered by bianca 2
·
0⤊
0⤋
Substract 2d in both sides of the equation
8d-4d-6d-8-2s = 2d-2d
The right side is 0
8d-4d-6d-8-2d = 0
Now add positive and negative terms:
Positives: only 8d
Negatives: 4d, 6d and 2d. Total: 12d
Now you have this
8d-12d - 8 = 0
You have 8d and you have to substract 12, so you will have a "deficit", the result is -4d. Consider that the d are dolars, positive dolars are the ones you have, negative dolars are the ones you owe me. So, you give me the 8 dolars and you tell me: tomorrow I give you 4 more. So, now you have -4d
The equation is this one:
-4d-8 = 0
Now add 8 to both sides of the equation
-4d-8+8 = 8 and -4d = 8
Lets multiply the equation by -1 (always both sides!)
4d = -8
And now lets divide by 4
4d divided by 4 is d
And -8 divided by 4 is done this way:
8/4 = 2
But you have a negative value, so the sign rule applies.
When you multiply or divide positive number, the result is positive.
The same when you multiply or divide negative numbers
But if one of them is negative and the other one is positive, the result is negative
So, d= -2
If you have more doubt, write to me
Ana
2007-01-18 06:39:26
·
answer #2
·
answered by MathTutor 6
·
0⤊
0⤋
8d-4d-6d-8=2d
To do this, you need to know :
The objective is to solve for the unknown which can be represent by any alphabet a to z and in this case it is d.
The rule when moving from left to rigth side of the equal (=) sign
Addtion become Subtraction
Subtaction become Addition
Multiplication become Divison
Divison become Multiplication
The above rule apply when you move from right to left as well.
There is not way out but to memorize the above and solving problem of this nature will be easy.
The easiest way for me is to move all the unknown onto left know and the digit onto rigth side.
8d-4d-6d-8=2d (move -8 over to right to become +8 and move +2d to left side to become -2d)
8d-4d-6d-2d=8
-4d=8 (move *4 over to right to become /4)
-d=(8/4)
-d=2 (move -d to right to become +d and +2 over to left to become-2)
d=-2
2007-01-18 08:36:27
·
answer #3
·
answered by cls22cls 2
·
0⤊
0⤋
hold on...
Step 1. Write the question out.
8d-4d-6d-8=2d
Step 2. Start simplifying
8d-4d-8= 8d
8d-8= 12d
8d=12d+8
-4d=8
d= -2
I think... I didn't really double check. It should be right though.
2007-01-18 06:31:20
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
passing all d´s to the first side and 8 to the second
8d-4d-6d-2d=8 -4d=8 d= -2
2007-01-18 06:28:37
·
answer #5
·
answered by santmann2002 7
·
0⤊
0⤋
8d - 4d - 6d - 8 = 2d
8d - 4d -6d -2d = 8
-4d = 8
d = 8/(-4)
d = -2 (answer)
2007-01-18 06:46:53
·
answer #6
·
answered by Tuhak 1
·
0⤊
0⤋